Sustainable Concrete Using Ground Granulated Blast Furnace Slag and Polypropylene Fibers: Flexural Behavior of RC Beams - Mardiana Oesman; Muhamad Irfan Nurdin; Muhammad Miftahul Riza; Wahib Hasan Prasetyo (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
As sustainability becomes a central focus in the construction industry, the combined use of supplementary cementitious materials and discrete fiber reinforcement offers an innovative pathway to enhance both environmental and structural performance. This study investigates the mechano-microstructural interaction between a dense Ground Granulated Blast Furnace Slag (GGBFS)–based matrix and polypropylene (PP) fibers in reinforced concrete (RC) beams, emphasizing the performance trade-offs among key mechanical properties. The experimental program comprised two phases. First, GGBFS replacement levels of 30% and 45% (by binder mass) were evaluated for compressive strength to identify the optimal matrix. Second, PP fibers were incorporated at 0, 3, 5, and 7 kg/m³ into the selected matrix. Tests under standardized curing conditions measured compressive strength, flexural load capacity, ductility, toughness, and stiffness. Microstructural analysis assessed fiber–matrix bonding quality and crack-bridging mechanisms. The 30% GGBFS mixture achieved the highest compressive strength in the optimization phase. Fiber inclusion produced distinct performance trade-offs: 3 kg/m³ delivered the best combination of strength and toughness, 5 kg/m³ maximized ductility, and 7 kg/m³ yielded the highest initial stiffness but slightly reduced post-peak energy absorption. These findings demonstrate that no single fiber dosage is universally optimal; instead, the choice should be based on prioritizing specific performance criteria. Microstructural observations revealed dense interfacial transition zones and effective fiber anchorage in GGBFS-rich matrices, enhancing crack control and delaying propagation. This study’s primary contribution lies in establishing a clear link between microstructural features and quantified mechanical trade-offs, providing a framework for performance-based mix design. The identified trade-offs also offer direct guidance for performance-based design, enabling engineers to tailor mix compositions to targeted applications such as seismic resilience, deflection-sensitive spans, or impact-resistant members.